Turkish sentiment analysis: a comparative study on different sentiment dictionaries with generated features and presenting a new sentiment dictionary - ALTINEL GİRGİN, AYŞE BERNA (My University, 2023)
Sentiment analysis is a research area that aims to find out people\"s opinions by matching data to topics, notions, etc. There are several approaches for sentiment analysis (e.g., machine learning-based, dictionary-based, hybrid-based, etc.). In this study, we presented a new tripolar Turkish sentiment dictionary, SentiMenTR, which consists of bigrams and unigrams. To compare the performances of SentiMenTR and other Turkish sentiment dictionaries (SWNetTR++ and SentiTurkNet), we conducted experiments on two Turkish datasets containing documents labeled as negative or positive. For experiments, firstly, we vectorized the documents by features extracted using polarity scores belonging to dictionaries. Afterward, we fitted machine learning models with these features. According to the experiment results, SentiMenTR performed better than other dictionaries. We aim to extend our dictionary, develop a negation handler module, and conduct more comprehensive experiments with deep learning methods in the future.
Keywords: Tıp; Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgisayar Bilimleri; Algoritmalar; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Mühendislik ve Teknoloji; Medicine; Social Sciences and Humanities; Sociology; Library Sciences; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Computer Sciences; algorithms; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Klinik Tıp; Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; TIBBİ BİLİŞİM; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; ENERJİ VE YAKITLAR; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Social Sciences (SOC); CLINICAL MEDICINE; COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; MEDICAL INFORMATICS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENERGY & FUELS; INFORMATION SCIENCE & LIBRARY SCIENCE; Yapay Zeka; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Bilgisayarla Görme ve Örüntü Tanıma; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Enerji Mühendisliği ve Güç Teknolojisi; Tıbbi Bilişim; Artificial Intelligence; Physical Sciences; Computer Science Applications; Computer Vision and Pattern Recognition; Information Systems and Management; Social Sciences & Humanities; Energy Engineering and Power Technology; Health Informatics; Machine Learning; Natural Language Processing; Opinion Mining; Sentiment Analysis; Turkish Sentiment Dictionary